Potentiation of epidural lidocaine by co-administering tramadol by either intramuscular or epidural route in cats - Hermeto, Larissa C. [UNESP]; DeRossi, Rafael; Marques, Beatriz C.; Jardim, Paulo H. A. (Canadian Vet Med Assoc, 2015)
This study investigated the analgesic and systemic effects of intramuscular (IM) versus epidural (EP) administration of tramadol as an adjunct to EP injection of lidocaine in cats. Six healthy, domestic, shorthair female cats underwent general anesthesia. A prospective, randomized, crossover trial was then conducted with each cat receiving the following 3 treatments: EP injection of 2% lidocaine [LEP; 3.0 mg/kg body weight (BW)]; EP injection of a combination of lidocaine and 5% tramadol (LTEP; 3.0 and 2.0 mg/kg BW, respectively); or EP injection of lidocaine and IM injection of tramadol (LEPTIM; 3.0 and 2.0 mg/kg BW, respectively). Systemic effects, spread and duration of analgesia, behavior, and motor blockade were determined before treatment and at predetermined intervals afterwards. The duration of analgesia was 120 +/- 31 min for LTEP, 71 +/- 17 min for LEPTIM, and 53 +/- 6 min for LEP (P < 0.05; mean +/- SD). The cranial spread of analgesia obtained with LTEP was similar to that with LEP or LEPTIM, extending to dermatomic region T13-L1. Complete motor blockade was similar for the 3 treatments. It was concluded that tramadol produces similar side effects in cats after either EP or IM administration. Our findings indicate that EP and IM tramadol (2 mg/kg BW) with EP lidocaine produce satisfactory analgesia in cats. As an adjunct to lidocaine, EP tramadol provides a longer duration of analgesia than IM administration. The adverse effects produced by EP and IM administration of tramadol were not different. Further studies are needed to determine whether EP administration of tramadol could play a role in managing postoperative pain in cats when co-administered with lidocaine after painful surgical procedures.